Electrostatic Field Tensities near Irregularities of Porous Silicon Surface - M. I. Terebinska; V. V. Lobanov; A. G. Grebenyuk (Хімія, фізика та технологія поверхні)
Equilibrium spatial structure of the Si89(OH)43H*36 cluster model simulated for a pyramid-like formation on porous silicon surface has been calculated within the frameworks of density functional theory method with 6-31G** basis set. The electron charge and electrostatic field distribution have been evaluated in the vicinity of such a formation. The electrostatic field tensity has been found to be great enough to ionize adsorbed organic molecules.